Synthesis of functionalized β-keto arylthioethers by the aryne induced [2,3] Stevens rearrangement of allylthioethers - Thangaraj, Manikandan; Gaykar, Rahul N.; Roy, Tony; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
A mild and transition-metal-free synthesis of β-keto arylthioethers has been developed by the aryne triggered [2,3] Stevens rearrangement of allylthioethers. The key sulfur ylide intermediate for the rearrangement was formed by the S-arylation of allylthioethers with arynes generated from 2-(trimethylsilyl)aryl triflates using CsF. Later, the reaction products are converted into valuable heterocycles in two steps.

Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.

Aryne Sommelet-Hauser rearrangement - Roy, Tony; Gaykar, Rahul N.; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemical Communications, 2019)
An aryne induced transition-metal-free and mild Sommelet-Hauser rearrangement of tertiary benzylamines for the synthesis of -aryl amino acid derivatives in moderate to good yields is presented. Unlike the conventional Sommelet-Hauser rearrangement of ammonium salts, the methodology developed herein requires neither harsh conditions nor strong bases. Moreover, a temperature dependent switchable selectivity for the Sommelet-Hauser and Stevens [1,2] rearrangements has been observed.

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions